MANAGEMENT POLICIES AND OHSMS IMPLEMENTATION: A CASE STUDY OF PT CAHAYA AGUNG DIRGAYASA - Fadhilah, Daffa Ino; Palupi, Majang (Jurnal Apresiasi Ekonomi, 2026)
This study aims to analyze the implementation of the Occupational Safety and Health Management System (OSHMS) program and the role of management policies on employee performance at PT Cahaya Agung Dirgayasa, a high-risk construction company. Using a qualitative method through a case study approach, data were collected through interviews, observations, and documentation from three key informants representing the strategic, managerial, and operational levels. Thematic analysis results indicate that the company has a structured OSHMS policy framework, encompassing mandatory PPE use and Toolbox Meetings. However, its implementation still faces significant obstacles, namely low employee awareness and understanding, inconsistent training programs, and the absence of dedicated OSH experts (safety officers). Despite these challenges, the implementation of the OSHMS has been proven to have a real positive impact. This includes increased motivation and work discipline, operational efficiency through reduced non-technical costs due to accidents, and a significant decrease in the number of work incidents. These findings confirm that management commitment to strengthening OSH culture is a crucial factor in optimizing employee performance.